Understanding and Targeting Indonesian Young Adult Internet Users - Chang, Andreas (Binus Business Review, 2010)
As the number of global internet users increases, companiesâ online advertisement expenditure also grows rapidly. Companies face challenges in targeting the right customers. Understanding which websites are often visited by target users and what they do on the internet will help companies direct their online advertisement to the right target. Using questionnaires, this study examines which sites are most often visited by Indonesian young adult internet users and what they do on the internet. It aims to understand the patterns of behavior of these users. The findings of this study provide some understanding to the marketers. Of consequence, such understanding would help them to select where and what to do with their advertisements when they are targeting the young adult internet users in Indonesia.Â